Aerodynamic Forces Affecting the H-Rotor Darrieus Wind Turbine. (11th January 2020) - Alqurashi, Faris; Mohamed, M. H.
Abstract : Darrieus wind rotor is a vertical axis wind turbine that is a very promising kind of wind converters at remote and domestic locations that have soft and weak wind potential and speed, but from the quantitative comparison with horizontal axis wind turbines, this type of turbines has a weak performance. Additional researches are still needed to develop its efficiency to identify all the requirements of the generated power in low power demands. The aim of the current investigation is to analyze all the acting forces on the main parts of Darrieus rotor over the rotations as well as in maintenance and stationary conditions. Aerodynamic forces assessment will be executed for 3 different blade shapes (nonsymmetric and symmetric airfoils) like the airfoil section shapes of the Darrieus rotor blades. NACA 0021, LS413, and S1046 are selected as cross-sectional profile in this work. CFD simulations have been used in this work to get the different aerodynamic forces on the rotor blades of the Darrieus turbines. The present results indicated that the symmetric S1046 blade has higher forces during the rotation and stagnant (static) conditions. Moreover, the self-starting capability of NACA 0021 is better than S1046 due to low aerodynamic torsion on the S1046 blades.